Investigation on the association between inerleukin-10 -592C/A, 819C/T and -1082A/G gene polymorphisms and development of diabetic nephrophathy - Yin, Qingfeng (Int J Clin Exp Pathol, 2015)
We conducted a case-control study to investigate the association between interleukin (IL)-10-592C/A, -819C/T and -1082A/G polymorphisms and susceptibility to diabetic nephropathy. A hospital-based case-control study was taken in our study. A total of 172 patients with proven type 2 diabetes mellitus and 344 controls were recruited from the First Affiliated Hospital of Xinxiang Medical University between March 2012 and October 2014. Genotyping of IL-10 -592C/A, -819C/T and -1082A/G polymorphisms was done by done by PCR-RFLP methods. By the χ(2) test, the distributions of the GG, GA and AA genotypes in IL-10 -1082A/G were significantly different between patients with diabetic nephropathy and control subjects (χ(2) = 8.09, P = 0.02). By conditional logistic regression analysis, we found that the AA genotype of IL-10 -1082A/G was associated with an elevated risk of diabetic nephropathy compared to the GG genotype in codominant model, and the adjusted OR (95% CI) was 2.38 (1.23-4.57). In dominant model, the GA+AA genotype was associated with a significantly increased risk of diabetic nephropathy compared to the GG genotype in dominant model (OR = 1.47, 95% CI = 1.05-2.16). In recessive model, the AA genotype could influence the susceptibility to diabetic nephropathy when compared with the GG+GA in recessive model (OR = 2.08, 95% CI = 1.12-3.85). In conclusion, we suggested that IL-10 -1082A/G gene polymorphism was correlated with development of diabetic nephropathy, but no association was observed between IL-10 -819T/C and -592A/C and risk of diabetic nephropathy.